Predictors of visual outcome following surgery in sellar lesions - S Devika; Sandhya Somasundaran; Charmaine Bridgette Solomon; Poothatta Jyothi (Kerala Journal of Ophthalmology, 2023)
Purpose: The purpose of the study is to find out the factors affecting visual outcome after surgery in patients with sellar lesions. Methods: We prospectively analyzed 36 patients diagnosed with sellar tumors who underwent surgery between July 2018 and January 2020. Clinical and demographic data including age, sex, pre- and post-operative visual acuity, visual field, and fundus examination was done in these patients. Size of the tumor was also measured radiologically. The size of the tumor was categorized as <2 and ≥2 cm. Results: Larger tumors had significant association with optic disc changes and visual field defects. The mean visual acuity (LogMAR) and field defects (mean deviation) improved postsurgery (paired t-test). Five of the six patients with peripheral constriction showed an improvement in the visual fields after surgery while only one of 15 patients with temporal hemianopia showed improvement in visual fields after surgery (P = 0.009). Patients with a tumor size <2 cm had statistically significant improvement in visual acuity (paired t-test P < 0.001) and visual fields (paired t-test P = 0.008. Conclusion: Tumor size <2 cm was found to be a good predictor of visual outcome after surgery.